Lymphokine-activated-killer-mediated lysis of cells infected with typhus group rickettsiae can be inhibited by OKT3 monoclonal antibody. - Carl, M (1986)
We examined the ability of monoclonal antibodies directed against lymphocyte surface antigens to block the lysis of typhus group rickettsia-infected cells by lymphokine-activated killer effectors. Lysis was significantly inhibited by OKT3 monoclonal antibody but not by OKT4 or OKT8 monoclonal antibody.